2020
DOI: 10.1097/phh.0000000000001202
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Prevention and Control Public Health Strategies in Shanghai, China

Abstract: Context: COVID-19 was characterized as a pandemic by the World Health Organization on March 11, 2020. This research aims to analyze the public health strategies to prevent and control COVID-19 in Shanghai, China, and provide recommendations for public health policy and interventions in the United States. Program: Based on the Social-Ecological Model, this research collected information for public health strategies from the Shanghai Municipal Health Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 5 publications
2
37
0
3
Order By: Relevance
“…The participants who opted not to go out to public places and wore a mask were considered as firstline prevention in contracting the virus. These findings are in concert with the previous studies conducted in other Asian countries (Ferdous et al, 2020;Neupane et al, 2020;Sulistyawati et al, 2021;Widayati, 2021;Zhang et al, 2020;Zhong et al, 2020;Zhou et al, 2020). The early onset of the pandemic, the Philippines' Department of Health continued the information dissemination campaigns about the importance of handwashing, covering of nose and mouth while coughing and sneezing, use of sanitizers, use of face masks, avoiding contact of fingers with mouth, nose, and eyes (Philippine Daily Inquirer, 2020; Republic of the Philippines, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The participants who opted not to go out to public places and wore a mask were considered as firstline prevention in contracting the virus. These findings are in concert with the previous studies conducted in other Asian countries (Ferdous et al, 2020;Neupane et al, 2020;Sulistyawati et al, 2021;Widayati, 2021;Zhang et al, 2020;Zhong et al, 2020;Zhou et al, 2020). The early onset of the pandemic, the Philippines' Department of Health continued the information dissemination campaigns about the importance of handwashing, covering of nose and mouth while coughing and sneezing, use of sanitizers, use of face masks, avoiding contact of fingers with mouth, nose, and eyes (Philippine Daily Inquirer, 2020; Republic of the Philippines, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Also, the more positive attitudes that the general population has, the more they would advocate preventive measures. Other studies found similar results (Ferdous et al, 2020;Neupane et al, 2020;Sulistyawati et al, 2021;Widayati, 2021;Zhang et al, 2020;Zhong et al, 2020;Zhou et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
“…A larger study that incorporates data from the whole country may be able to demonstrate such a correlation. Overall, these data that demonstrate a reduction in COVID-19 infections to near zero by the end of lockdown further support the successful nature of the restriction orders utilized in controlling transmission of COVID-19 in Shanghai (53).…”
Section: Discussionmentioning
confidence: 53%
“…Students who came from high-risk areas must be conducted home or centralized health surveillance for 14 days. The above measures were also applicable to the prevention of influenza and other respiratory diseases [29,30]. In our study, we found that the proportion of pediatric patients with respiratory infections among total outpatients, the number of completed tests for respiratory viruses and the corresponding positive cases of ADV, FluA, FluB, and RSV did not elevate in March and April compared with the same periods in 2018 and 2019.…”
Section: Discussionmentioning
confidence: 56%